2013
DOI: 10.1159/000353734
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptional Analysis of <b><i>Drosophila</i></b> Larvae Infected by Entomopathogenic Nematodes Shows Involvement of Complement, Recognition and Extracellular Matrix Proteins

Abstract: Heterorhabditis bacteriophora is an entomopathogenic nematode (EPN) which infects its host by accessing the hemolymph where it releases endosymbiotic bacteria of the species Photorhabdus luminescens. We performed a genome-wide transcriptional analysis of the Drosophila response to EPN infection at the time point at which the nematodes reached the hemolymph either via the cuticle or the gut and the bacteria had started to multiply. Many of the most strongly induced genes have been implicated in immune responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 49 publications
3
111
0
Order By: Relevance
“…Nematode infections were performed in duplicate in 96-well plates as described previously, and analyzed using the Student t test [4] .…”
Section: Nematode Infectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nematode infections were performed in duplicate in 96-well plates as described previously, and analyzed using the Student t test [4] .…”
Section: Nematode Infectionsmentioning
confidence: 99%
“…Age-matched third-instar larvae (96 h after egg-laying) were analyzed. For the control and mutant genotypes, we used samples infected by EPNs for 2 h and analyzed these 6 h afterwards as described in the study by Arefin et al [4] . The summary of the microarray analysis is shown in online supplementary table S6.…”
Section: Experimental Design and Preparation Of Microarray Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the nematode and its bacterial endosymbiont appear to inhibit some aspects of AMP production, melanization, encapsulation, and phagocytosis (11,(16)(17)(18). Studies using D. melanogaster larvae as a model host for the EPN Heterorhabditis bacteriophora and its endosymbiont Photorhabdus luminescens have shown that infection induces expression of a large number of immune genes, including AMPs, and that AMP expression is primarily a response to the bacterial endosymbiont rather than to the nematode (4,19). Infection also stimulates clotting, and clotting mutants show decreased survival in response to H. bacteriophora-P. luminescens infection (20,21).…”
mentioning
confidence: 99%